Research case data conceptology with the paradigmatic and syntagmatic maintenance - Abdullaev, Sapiya-hanum M. Temirbulatova, Majeed Sh. Khalilov, Sabrina H. Shikhaliyeva, Iza J. (Opción, 2019)
The purpose of the article is to investigate research case data conceptology with the paradigmatic and syntagmatic maintenance. The methodology stylistically the played out interpretation of the case description allows classifying the field of abessive with the maintenance of a peripheral and core zone of a concept. The main results Semantic field of abessive in the studied languages does not function isolated, and enters the hierarchical system of case data conceptology. In conclusion, each model of the natural speech use, verbalizing experience of linguocultural community of the Nakha-Dagestan languages, distinguishes core and peripheral units of emotional concepts.